Recovery of antifungal peptides from zophobas morio fabricus - Faruck, Mohammad Omer; Yusof, Faridah; Chowdhury, Silvia (2015)
Human has strong natural immunity against fungal infections, nevertherless, fungi can cause diseases when this immunity breaks down, such as in cancer patients, transplant recipients and acquired immunodeficiency syndrome (AIDS) patients. In the last few years, fungal infections have increased strikingly and it has been blamed for the rise in the number of deaths in patients with compromised immune systems. Antifungal remedy from the natural sources is preferred because chemical treatments maybe toxic to both fungus as well as human cells. In this study, antifungal peptides has been recovered from whole body extraction of non-immunized final instar larvae of Zophobas morio Fabricus using acidified (triflouroacetic acid) solvent (ethanol and isopropanol). The two different extracts were found active, although at varying degrees, towards four fungi tested, namely, Aspergillus niger, Microsporum canis, Candida albicans and Blastomyces dermatitids. In vitro susceptibility results were observed by ‘Colony Count Method’ and this was then compared and confirmed by two other assay methods, namely ‘Poisoned Agar Assay’ and ‘EUCAST Standard Method or Broth Micro Dilution Method’ of the European Center for Disease Prevention and Control. Results showed that the two different extracts exhibited high activity towards the tested fungi, whereby, isopropanolic extract against C. albicans showed the highest inhibition (82%). Besides, results obtained from the other two assay methods showed almost similar trend in activities. This work may present the first initiative towards recovering antifungal peptides from low cost, easily found insect larvae, whereby it can be potentially developed as peptide-based drug to combat fungal infection. Future work includes purifying, identification and characterization of peptides.